Barriers and facilitators to the transplant process among patients living with polycystic kidney disease: a qualitative Approach - Smith, Juliana; Harris, Orlando O.; Adey, Deborah; Park, Meyeon (BMC nephrology, 2023)
Background Kidney transplant is the gold standard for renal replacement therapy in patients with autosomal dominant polycystic kidney disease (ADPKD), which is the fourth leading cause of kidney failure. Despite the medical and economic benefits of preemptive kidney transplant over dialysis before transplant, only 9–21% of qualifying patients receive preemptive transplants. Given the low rates of preemptive transplant, the aim of this study was to determine perceived facilitators and barriers to preemptive transplant among ADPKD patients using a qualitative approach. Methods Data were collected between July 2021 and January 2022 from virtual individual semi-structured interviews of 16 adult participants with ADPKD. Qualitative analysis of the recorded interviews was conducted to generate themes. Results Our findings revealed two themes specific for facilitators to preemptive transplant (social support and patient agency) and three themes specific to barriers for preemptive transplant (inadequate social support, gaps in knowledge, and institutional and systemic policies). The results also include various subthemes and the application of these themes to the social ecological model. Conclusions These findings suggest that increasing social support and patient agency, such as through patient navigator programs and encouraging effective communication between health care providers and patients, can facilitate the transplant process. Increasing dissemination of transplant knowledge from institutions and systems to patients through paired kidney exchange education and live donor outreach can also increase timely access to preemptive kidney transplants for patients with ADPKD. Our findings are limited by our single site study in the US, which may not apply to individuals experiencing different social, cultural, and health access conditions.